Coding and decoding of calcium signals in plants - Luan, Sheng; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
Plants cannot move away from their environments. As a result, all plants that have survived to date have evolved sophisticated signaling mechanisms that allow them to perceive, respond, and adapt to constantly changing environmental conditions. Among the many cellular processes that respond to environmental changes, elevation of calcium levels is by far the most universal messenger that matches primary signals to cellular responses. Yet it remains unclear how calcium, a simple cation, translates so many different signals into distinct responses - how is the ?specificity? of signal-response coupling encoded within the calcium changes?
Plant cell calcium, past and future / Anthony J. Trewavas -- Calcium signalilng and homeostasis in nuclei / Christian Mazars .. [et al.] --Interactions between calcium and ROP signaling regulate pollen tube tip growth / Augusta Jamin and Zhenbiao Yang -- Calcium, mechanical signaling, and tip growth / Won-Gyu Choi, Sarah J. Swanson, and Simon Gilroy -- Calcium signals in the control of stomatal movements / Alex A.R. Webb and Fiona C. Robertson -- Stimulus perception and membrane excitation in unicellular alga Chlamydomonas / Kenjiro Yoshimura -- Cyclic nucleotide gated channels (CNGCs) and the generation of Ca2+ signals / Wei Ma and Gerald A. Berkowitz -- Annexins / Anuphon Laohavisit and Julia M. Davies -- Structure and function of CDPK : a sensor responder of calcium / Yohsuke Takahashi and Takeshi Ito -- Elucidation of calcium-signaling components and networks / Irene S. Day and A.S.N. Reddy -- Decoding of calcium signal through calmodulin : calmodulin-binding proteins in plants / Liqun Du ... [et al.] / The CBL-CIPK network for decoding calcium signals in plants / Oliver Batistic ... [et al.]
Electronic reproduction.
Keywords: Plant cellular signal transduction; Plants -- Effect of calcium on; Calcium channels; Electronic books